2022
DOI: 10.52403/ijhsr.20221017
|View full text |Cite
|
Sign up to set email alerts
|

Dyslipidemia in Prediabetes Population: A Retrospective Study of 91780 Cases

Abstract: Dyslipidemia over time leads to atherogenesis in both diabetics as well as prediabetics. The study aims to assess the correlation if any between the blood glucose levels [HbA1c] and the lipid cholesterol levels among the prediabetes group. Method: A total of 91780 cases were reviewed across India from the same group of laboratory across 7 years from Jan 2015 to May 2022. The lipid profiles and glycated haemoglobin [HbA1c] were tested in all of them. The separation and quantification of hemoglobin A1c (HbA1c) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…[16] Furthermore, numerous studies have found a link between diabetes, particularly type 2, and dyslipidemia, [17,18] whereas other studies have found a link between prediabetes and dyslipidemia. [19] This study aimed to investigate the relationship between vitamin D levels, glycemic status, IR, and lipid profiles in a prediabetic versus nondiabetic Saudi population.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[16] Furthermore, numerous studies have found a link between diabetes, particularly type 2, and dyslipidemia, [17,18] whereas other studies have found a link between prediabetes and dyslipidemia. [19] This study aimed to investigate the relationship between vitamin D levels, glycemic status, IR, and lipid profiles in a prediabetic versus nondiabetic Saudi population.…”
Section: Introductionmentioning
confidence: 99%
“…[16] Furthermore, numerous studies have found a link between diabetes, particularly type 2, and dyslipidemia, [17,18] whereas other studies have found a link between prediabetes and dyslipidemia. [19]…”
Section: Introductionmentioning
confidence: 99%